Value pluralism about sexual intimacy in residential care. (May 2023) - Schouten, Vanessa; Henrickson, Mark; Cook, Catherine M; MacDonald, Sandra; Atefi, Narges
Background: The existing literature on sexuality and intimacy in residential care tends to focus on either the question of rights, or the value of autonomy. Where the literature does reference values other than autonomy, such values are considered in the context of being a guide to whether or not a resident is autonomous, rather than being important values in their own right. Objective: This paper draws on qualitative data gathered as part of a larger study in order to inform practice on how care workers respond to intimacy issues that arise with residents with dementia and to inform a general ethics of sex and sexuality, demonstrating that an approach which permits value pluralism can be appropriate in certain contexts. Research Design: The qualitative data referred to in this paper was gathered from semi-structured interviews undertaken as part of a larger mixed-method research project. The interview text was analysed using Thorne's methodological approach, interpretive description. Participants and research context: The qualitative arm of the project consisted of semi-structured interviews conducted between October 2018 and October 2019 with participants (staff, residents and family members) recruited from 35 residential care homes in Aotearoa New Zealand. Ethical Considerations: Participation was informed, voluntary and written consent was gained before interviews. The project was approved by the Massey University Human Ethics Committee (Northern), number NOR 18/25. Findings: Analysis of the scenarios presented in this paper shows that decision-making around sexual intimacy involving people with dementia in a residential care setting is complex and requires recognizing and weighing the different values that may be a in play. Conclusion: A focus on safety and consent to the exclusion of other values which matter morally in this context is a mistake which prevents care workers from providing appropriately person-centred care to residents, as policies which focus on the goal of care allow space for critical examination of issues which are likely to be highly context-sensitive.